Protease‐modulating polyacrylate‐based hydrogel stimulates wound bed preparation in venous leg ulcers – a randomized controlled trial. (26th February 2014) - Humbert, P.; Faivre, B.; Véran, Y.; Debure, C.; Truchetet, F.; Bécherel, P.‐A.; Plantin, P.; Kerihuel, J.‐C.; Eming, S.A.; Dissemond, J.; Weyandt, G.; Kaspar, D.; et al.
Abstract Background Stringent control of proteolytic activity represents a major therapeutic approach for wound‐bed preparation. Objectives We tested whether a protease‐modulating polyacrylate‐ (PA‐) containing hydrogel resulted in a more efficient wound‐bed preparation of venous leg ulcers when compared to an amorphous hydrogel without known protease‐modulating properties. Methods Patients were randomized to the polyacrylate‐based hydrogel (n = 34) or to an amorphous hydrogel (n = 41). Wound beds were evaluated by three blinded experts using photographs taken on days 0, 7 and 14. Results After 14 days of treatment there was an absolute decrease in fibrin and necrotic tissue of 37.6 ± 29.9 percentage points in the PA‐based hydrogel group and by 16.8 ± 23.0 percentage points in the amorphous hydrogel group. The absolute increase in the proportion of ulcer area covered by granulation tissue was 36.0 ± 27.4 percentage points in the PA‐based hydrogel group and 14.5 ± 22.0 percentage points in the control group. The differences between the groups were significant (decrease in fibrin and necrotic tissue P = 0.004 and increase in granulation tissue P = 0.0005, respectively). Conclusion In particular, long‐standing wounds profited from the treatment with the PA‐based hydrogel. These data suggest that PA‐based hydrogel dressings can stimulate normalization of the wound environment, particularly in hard‐to‐heal ulcers.